2020
DOI: 10.1177/1352458520912170
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of rituximab originator (MabThera®) to biosimilar (Truxima®) in patients with multiple sclerosis

Abstract: Background: Rituximab’s originator MabThera® or Rituxan® has demonstrated high efficacy in multiple sclerosis (MS). Because of the patent expiration, rituximab biosimilars have been developed. However, because a biosimilar is not the exact copy of the originator, the efficacy and safety of a biosimilar may significantly differ. Objectives: To compare the efficacy and safety of the biosimilar Truxima® and the originator MabThera® in MS. Methods: Consecutive MS patients receiving MabThera® or Truxima® were prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Phase III clinical trials in rheumatoid arthritis and lymphoma revealed similar pharmacodynamics, immunogenicity, and safety profiles between MabThera and Truxima (12). Similarly, in patients with immune thrombocytopenic purpura (13) and multiple sclerosis (14), there were no differences between the biosimilar and the originator in clinical outcomes, infective complications, infusion reactions, and B-cell depletion. In addition, several second generation anti-CD20 drugs are in development.…”
Section: Discussionmentioning
confidence: 93%
“…Phase III clinical trials in rheumatoid arthritis and lymphoma revealed similar pharmacodynamics, immunogenicity, and safety profiles between MabThera and Truxima (12). Similarly, in patients with immune thrombocytopenic purpura (13) and multiple sclerosis (14), there were no differences between the biosimilar and the originator in clinical outcomes, infective complications, infusion reactions, and B-cell depletion. In addition, several second generation anti-CD20 drugs are in development.…”
Section: Discussionmentioning
confidence: 93%
“…Since a biosimilar is not the exact copy of the originator, its efficacy and safety may significantly differ. For these reasons, a recent study tested the equivalence of the RTX biosimilar CT-P10 and its originator RTX used for MS treatment in terms of efficacy, safety, and tolerability [178]. Concerning efficacy, similar CD19 + lymphocyte depletion, relapse rate and evolution of MRI activity were observed between the two groups of treatment.…”
Section: Biosimilarsmentioning
confidence: 99%
“…Results suggest that CT-P10 could represent a relatively cheaper and safe therapeutic alternative and could improve access to a highly efficient therapy for MS in low-or middleincome countries. Recently, a prospective study demonstrated the equivalence of the RTX biosimilar Truxima® compared to its originator MabThera® in terms of efficacy, safety, and tolerability in a MS population [178]. Clinical use in other neurological disorders RTX has been approved for the treatment of B-cell lymphomas (i.e., non-Hodgkin's lymphoma, chronic lymphatic leukemia) in 1997.…”
Section: Biosimilarsmentioning
confidence: 99%
“…Perez et al. confirmed the similarity of rituximab originator and biosimilar in 145 MS patients (RR and progressive) ( 98 ). Patients in the two groups did not differ in CD19+ lymphocyte counts at each follow-up examination and showed a comparable reduction in relapse rate at 12 months (from 0.50 to 0.02 for originator and from 0.40 to 0.025 for biosimilar), whereas EDSS remained stable in both groups at 6 and 12 months.…”
Section: Introductionmentioning
confidence: 93%